2005
DOI: 10.1164/rccm.200404-531oc
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib as a Novel Antifibrotic Agent in Bleomycin-induced Pulmonary Fibrosis in Mice

Abstract: Imatinib mesylate is a potent and specific tyrosine kinase inhibitor against c-ABL, BCR-ABL, and c-KIT, and has been demonstrated to be highly active in chronic myeloid leukemia and gastrointestinal stromal tumors. We examined the antifibrotic effects of imatinib using a bleomycin-induced lung fibrosis model in mice because imatinib also inhibits tyrosine kinase of platelet-derived growth factor receptors (PDGFRs). Imatinib inhibited the growth of primary murine lung fibroblasts and the autophosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 29 publications
6
171
2
Order By: Relevance
“…), Cytokines (Interferon-β (Azuma, Li et al, 2005), Interferon-γ (Gurujeyalakshmi & Giri, 1995;Hyde, Henderson, Giri, Tyler, & Stovall, 1988;Okada, Sugie, & Aisaka, 1993), Interleukin (IL)-1beta (M. Yasui et al, 1991), IL-10 (Arai et al, 2000), IL-18 (Nakatani-Okuda et al, 2005), Keratinocyte growth factor (Deterding et al, 1997;Sugahara, Iyama, Kuroda, & Sano, 1998;Yi et al, 1996), Hepatocyte growth factor (Dohi, Hasegawa, Yamamoto, & Marshall, 2000;Mizuno, Matsumoto, Li, & Nakamura, 2005;Umeda et al, 2004;Yaekashiwa et al, 1997), Chemokine ligand (CXCL)-10 (Tager et al, 2004),CXCL11 (Burdick et al, 2005), CD (cluster of differentiation)-36 (Yehualaeshet et al, 2000) etc. ), Cytokine antibodies (Transforming growth factor-β (Giri, Hyde, & Hollinger, 1993), Tumor necrosis factor-α (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006;Fujita et al, 2003;Piguet & Vesin, 1994), Connective tissue growth factor (Matsuoka et al, 2002), IL-12 , IL-13 (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006), Platelet derived growth factor (Aono et al, 2005;Chaudhary, Schnapp, & Park, 2006;Daniels et al, 2004;Yoshida et al, 1999), Vascular endothelial growth factor (Hamada et al, 2005), CCR-1 (Tokuda et al, 2000), CCR-3 (Huaux et al, 2005), CCL-11 (Huaux et al, 2005), CD-11 (Piguet, Rosen, Vesin, & Grau, 1993), MCP-1 etc. ), Chinese herbs (Feitai (Gong et al, 2004;Gong et al, 2005;…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
“…), Cytokines (Interferon-β (Azuma, Li et al, 2005), Interferon-γ (Gurujeyalakshmi & Giri, 1995;Hyde, Henderson, Giri, Tyler, & Stovall, 1988;Okada, Sugie, & Aisaka, 1993), Interleukin (IL)-1beta (M. Yasui et al, 1991), IL-10 (Arai et al, 2000), IL-18 (Nakatani-Okuda et al, 2005), Keratinocyte growth factor (Deterding et al, 1997;Sugahara, Iyama, Kuroda, & Sano, 1998;Yi et al, 1996), Hepatocyte growth factor (Dohi, Hasegawa, Yamamoto, & Marshall, 2000;Mizuno, Matsumoto, Li, & Nakamura, 2005;Umeda et al, 2004;Yaekashiwa et al, 1997), Chemokine ligand (CXCL)-10 (Tager et al, 2004),CXCL11 (Burdick et al, 2005), CD (cluster of differentiation)-36 (Yehualaeshet et al, 2000) etc. ), Cytokine antibodies (Transforming growth factor-β (Giri, Hyde, & Hollinger, 1993), Tumor necrosis factor-α (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006;Fujita et al, 2003;Piguet & Vesin, 1994), Connective tissue growth factor (Matsuoka et al, 2002), IL-12 , IL-13 (Fichtner-Feigl, Strober, Kawakami, Puri, & Kitani, 2006), Platelet derived growth factor (Aono et al, 2005;Chaudhary, Schnapp, & Park, 2006;Daniels et al, 2004;Yoshida et al, 1999), Vascular endothelial growth factor (Hamada et al, 2005), CCR-1 (Tokuda et al, 2000), CCR-3 (Huaux et al, 2005), CCL-11 (Huaux et al, 2005), CD-11 (Piguet, Rosen, Vesin, & Grau, 1993), MCP-1 etc. ), Chinese herbs (Feitai (Gong et al, 2004;Gong et al, 2005;…”
Section: Drug Intervention Studies In the Bleomycin Modelmentioning
confidence: 99%
“…7,8 In contrast, SC administration, either by repeated injections or mini pumps is known to induce a more heterogeneous distal fibrosis, often located in the subpleural compartment, with vascular involvement. 9 In this model acute inflammation peaks around 1-2w 10,11 and skin fibrosis initiated by this route of administration are known to persist at least 6w after cessation of bleomycin. 12 If anything, the lung is even more sensitive to bleomycin than skin, as demonstrated by the occurrence of lung alterations before alterations in skin, despite the skin being the site of injection.…”
mentioning
confidence: 99%
“…Indeed, EndoMT might substantially contribute not only to pathologic vascular remodeling in SSc, but also to dermal and internal organ fibrosis, as has recently been observed in experimental models of kidney and lung fibrosis (13,15). Previous studies have shown that blocking of c-Abl with imatinib mesylate could prevent, or induce regression of, dermal fibrosis in different mouse models of SSc and could attenuate bleomycin-induced pulmonary fibrosis in mice (24)(25)(26). However, whether these effects would depend on the abrogation or reversal of the EndoMT process is unknown.…”
Section: New Insights Into Endomt: C-abl Protein Kinase C␦ and Smalmentioning
confidence: 85%